Proceedings of the Ocean Drilling Program, 143 Scientific Results 1995
DOI: 10.2973/odp.proc.sr.143.243.1995
|View full text |Cite
|
Sign up to set email alerts
|

Karst Morphology and Diagenesis of the Top of Albian Limestone Platforms, Mid-Pacific Mountains

Abstract: The upper surface of the Albian platform limestone on many Mid-Pacific Mountains (MPM) guyots, as shown by multibeamsonar, bathymetric data, and seismic-reflection data from where pelagic sediments have buried the Albian platform limestone, shows that the top of the limestone sequence has been sculptured by streams, by waves, and by dissolution during an episode of emergence to heights of as much as 180 m above sea level. Seismic-reflection profiles show that the surface is arched over the buried volcanic base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…100.45 ± 1 Ma (marked by SS5). Our findings of two major karstification events before the demise may support the hypothesis of ‘death‐by‐emergence‐and‐submergence’ by Winterer et al (1995) and Winterer (1998).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…100.45 ± 1 Ma (marked by SS5). Our findings of two major karstification events before the demise may support the hypothesis of ‘death‐by‐emergence‐and‐submergence’ by Winterer et al (1995) and Winterer (1998).…”
Section: Discussionsupporting
confidence: 91%
“…The study has revealed clear evidence of two subaerial exposure events in the mid (105.15 ± 1 Ma) and late Albian (100.45 ± 1 Ma), which may support the hypothesis of ‘death‐by‐emergence‐and‐submergence’ by Winterer et al (1995) and Winterer (1998). Syndepositional fractures at the rims interacted with the subaerial exposure events by focusing the dissolution which formed vertically stacked flank‐margin fracture‐cave system.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations